STRATEGI GURU DALAM MENGEMBANGKAN KREATIVITAS SISWA MELALUI SENI BUDAYA DAN PRAKARYA DI SD 2 PANJUNAN - Syeh Priyadi; Muhammad Ilyas Fitrian; Wasis Wijayanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine teachers' strategies in developing fine arts learning towards student creativity at SD N 2 PANJUNAN KUDUS. Developing artistic creativity in children is an important aspect of overall education. Artistic creativity plays a vital role in children's development, helping them to express themselves, develop their imagination and strengthen their cognitive and motor skills. This research analyzes several strategies that can be used to stimulate children's artistic skills as well as the stages or syntax of PJBL learning according to The George Lucas Education Foundation, namely: 1. Determining basic questions 2. Developing a project plan 3. Developing a schedule 4. Monitoring students and project progress 5. Evaluation of results 6. Evaluation of experiences with this theory resulting in strategies used to help develop artistic creativity in students, namely by 1) play approach 2) project-based approach 3) sensory approach 4) modeling approach 5) integrated approach 6) open approach 7) reflective approach. With this approach strategy, it is hoped that it will be able to overcome problems at SD N 2 PANJUNAN regarding 1) lack of student knowledge, inappropriate curriculum. 2) limited learning time. 3) lack of support from parents to educate their children. And can develop their talents in arts and culture and crafts (SBDP).